2013
DOI: 10.1093/mnras/sts299
|View full text |Cite
|
Sign up to set email alerts
|

The ATLAS3D project – XVIII. CARMA CO imaging survey of early-type galaxies

Abstract: We present the Combined Array for Research in Millimeter Astronomy (CARMA) ATLAS 3D molecular gas imaging survey, a systematic study of the distribution and kinematics of molecular gas in CO-rich early-type galaxies. Our full sample of 40 galaxies (30 newly mapped and 10 taken from the literature) is complete to a 12 CO(1-0) integrated flux of 18.5 Jy km s −1 ‡, and it represents the largest, best-studied sample of its type to date. A comparison of the CO distribution of each galaxy to the g − r color image (r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
246
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 153 publications
(260 citation statements)
references
References 81 publications
13
246
1
Order By: Relevance
“…The first of these contaminants is optically obscuring dust, that is ubiquitously present in ETGs with molecular gas (Alatalo et al 2013). To minimise dust extinction, our MGE models were constructed from HST F814LP images (the longest wavelength available).…”
Section: Luminous Mass Models Agn and Dustmentioning
confidence: 99%
“…The first of these contaminants is optically obscuring dust, that is ubiquitously present in ETGs with molecular gas (Alatalo et al 2013). To minimise dust extinction, our MGE models were constructed from HST F814LP images (the longest wavelength available).…”
Section: Luminous Mass Models Agn and Dustmentioning
confidence: 99%
“…A diverse range of observations and simulations was performed, at its core optical integralfield spectroscopic observations with the SAURON instrument (Bacon et al 2001), yielding detailed information on the stellar kinematics Emsellem et al 2011;Krajnović et al 2013a,b) and populations (Cappellari et al 2012;Scott et al 2013;McDermid et al 2014McDermid et al , 2015. In addition to single-dish molecular gas surveys (Combes et al 2007;, both H i and CO interferometric observations were obtained (Young et al 2008;Crocker et al 2011;Serra et al 2012;Alatalo et al 2013). The morphology and kinematics of the molecular gas are characterised in Davis et al (2013), while its physical conditions are discussed in Crocker et al (2012) and Bayet et al (2013).…”
Section: Atlas 3d Surveymentioning
confidence: 99%
“…This has been interpreted as being due to interactions with the group environments or a recent minor galaxy merger (Serra et al 2012). This percentage decreases when focusing on H 2 only (Alatalo et al 2013;Davis et al 2013). Lagos et al (2014b, hereafter Paper I) explored the origin of the H I and H 2 gas contents of ETGs using a semi-analytic model of galaxy formation and showed that the observed gas fractions in ETGs arise in the model due to inefficient replenishment of the gas in ETGs as a result of both ram-pressure stripping of the hot gas and heating by active galactic nuclei (AGN), which prevents gas cooling from the hot halo.…”
mentioning
confidence: 99%